Hubungan Media Informasi, Pengetahuan, Pendidikan, Pengalaman Dengan Tingkat Kecemasan Masyarat Di Massa Pandemi Covid-19 - Achmad Masfi; Miftahul Arifin (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2022)
The virus was first detected in Indonesia on March 2, 2020 and announced by President Joko Widodo, which caused anxiety. The purpose of this study was to analyze the relationship between information media, knowledge, education, experience, stigma and public anxiety during the covid 19 pandemic.The type of research used in this study is